R code and data for "Comparing multiple survey and recruitment-mortality models to assess growth rates and population projections" ... - Severud, William; DelGiudice, Glenn D; Bump, Joseph K (Data Repository for the University of Minnesota (DRUM), 2019)
This collection of files provides data and R code supporting the publication "Comparing survey and multiple recruitment-mortality models to assess growth rates and population projections" in Ecology and Evolution. We provide all necessary data not included in the manuscript to reproduce the analysis of growth rates and population projections of moose in northeastern Minnesota. ... : This collection of files provides data and R code supporting the publication "Comparing survey and multiple recruitment-mortality models to assess growth rates and population projections" in Ecology and Evolution. We provide all necessary data not included in the manuscript to reproduce the analysis of growth rates and population projections of moose in northeastern Minnesota. ...